Pytanie o pamięć. Relacje autobiograficzne więźniów obozów koncentracyjnych - Posłuszny, Łukasz; Greń, Paweł (Aureus, 2012)
This book consists of two main parts. The first part offers a basic methodological introduction, presenting a concise but multifaceted overview of current problems of collective memory. The second part contains a set of interviews with former prisoners of concentration camps carried out by the authors. The research was conducted by Paweł Greń and Łukasz Posłuszny and focuses on issues of collective and cultural memory illustrated by individual life experiences of concentration camps prisoners. The field of oral history serves as the framework of analysis and narrative inquiry as its research tool. Interviews and additional research materials were collected by the authors and are not available in previous publications, making this work a precious supplement to the current scholarly body of knowledge and achievements in the discipline of memory studies. According to the authors, current historical and literary publications provide an incomplete picture of the WWII and its aftermaths for survivors, because descriptions of the war and imprisonment in the camp play still a dominate role in narratives. The importance of these issues in autobiographies is unquestionable and highly needed to create a common identity among generation of prisoners, though authors often wanted to perceive the fate of individuals in a broader perspective – including the periods before and after the war. Hence, interviews stressed personal experiences and their understanding over time by former prisoners. The interviews covered many topics on life before, during and after the camp – among them daily and neutral routines, but also difficult matters. The latter were connected on the one hand with traumatic events or harsh memories and emotions, and on the other hand with less extensively highlighted threads of prisoners’ lives - such as issues of the body and sexuality – and their dependence on particular representation or narrative. The authors are convinced that the book serves not only as a record of past remembered by eyewitnesses, but it also depicts their accounts in wider contexts and discourses, which expose specific dimensions of told and written stories. In the book Questions for Memory one examine the approach proposed by young scholars. Interviews were conducted from 2009-2011, seventy years after the end of the second world war, and this initiative was the result of questions and doubts of the authors from the existing literature. They also wanted to use the unique opportunity to meet with eyewitnesses and record their stories, because when they pass away we will irretrievably lose the possibility to listen to them and to pose sensitive questions. The majority of the interviewees were prisoners of KL Auschwitz-Birkenau, and their experiences differed greatly from each other based on social background and specific experience in the camps as well as their post-camp and postwar life. Aside from persons whose stories are already well known and open, readers will hear the stories of those who spoke only reluctantly and very rarely, or who had remained silent until the present author’s research. Qualitative differences between interviews occurred on the level of established relationship and atmosphere of trust, which varied according to circumstances and individual character and personality. For P. Greń and Ł. Posłuszny, each interviewed person is equally and highly valued due to the collected material and the personal experience of the meetings. Among the ten interviews placed in the book, seven of them are the stories told by women. Their testimonies exemplify realities of everyday prisoners’ existence and gravitate towards mirroring specifically feminine perspectives of imprisonment. For women, crucial problems stemmed from experiences of body that intertwine with suffering, feeling of shame and humiliation. Early discussions on holocaust literature and issues of representation that shaped the Polish narrative and collective memory imposed imperatives of silence on certain topics. A solution for reconciling heroic and inhuman deeds in stories with completely human physiology was impossible and improper for many years. There were also questions about life after, ways of dealing with a trauma or reflections on the present time. During conversations the authors attempted to come closer to something distant and incomprehensible for their generation and for people who did not experience the camps. Despite the fact that there have been seventy years of dealing with these events in literature, art, drama, film, memoirs and scientific works, the past still breeds more questions than answers. The book Questions for Memory serves as an example of this phenomenon.
Questions for Memory. Autobiographical Accounts of Concentration Camps Prisoners
Keywords: gender studies; literature; narrative; Holocaust studies; biographical methods; concentration camps